(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The shortest path or length between any two nodes or vertices of the graph G is defined as the distance between those two vertices. The number of vertices that are adjacent to a particular vertex is defined to be the degree of that particular vertex.